Correlation Between Land Cover Change and the Spatial Distribution of Land Surface Temperature in Tanjungpinang City, Indonesia - Afriadi, Arie; Septio, Ghenady; Chidmahdjati, Aria Bagiasa; Saputri, Dea Rizky (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Land cover change is a global environmental issue driving the Urban Heat Island (UHI) effect, in which artificial surfaces experience higher temperatures than vegetated areas. Tanjungpinang City, the capital of the Riau Islands Province, has experienced rapid development driven by population growth, leading in the conversion of green spaces into settlements and infrastructure and increasing urban heat island (UHI) risks. This study analyzes changes in land cover and land surface temperature (LST) from 2003 to 2023 and examines their Correlation. Using Google Earth Engine (GEE), we processed Landsat and MODIS imagery and used correlation analysis to assess the relationship between land cover changes and land surface temperature (LST) dynamics. The results of the study indicate that during the 2003–2023 period, Built-up Land experienced a significant increase of 27.15 km², which inversely correlated with a reduction in Vegetation area by 14.02 km². This transformation triggered an expansion of areas categorized under high and very high land surface temperatures in Tanjungpinang City. Correlation and regression analyses confirm a strong negative relationship between Vegetation and LST, underscoring vegetation's crucial role in reducing heat through shading and evapotranspiration. Conversely, Built-up Land shows a strong positive correlation with LST, highlighting its contribution as a primary driver of surface heat. Meanwhile, Water Bodies and Bare Land exhibit more varied influences with relatively minor impacts on overall urban temperature fluctuations. In general, this research concludes that the conversion of vegetated land to Built-up Land is the main factor driving increases in surface temperatures in Tanjungpinang City. These findings are expected to serve as a strategic foundation for the local government in evaluating spatial planning policies and prioritizing the integration of Green Open Spaces to achieve sustainable urban planning that is adaptive to climate change.